Prokaryotic expression and antibacterial activity of antibacterial peptide Ranalexin gene from Rana catesbiana - XIE Fang; HAN Wen-yu; LEI Lian-cheng; HAN Jun-you; HU Bo (浙江大学学报. 农业与生命科学版)
In order to verify antibacterial activity of recombinant antibacterial peptide Ranalexin, the total RNA was extracted from the skin of Rana catesbiana and the ranalexin gene was amplified by RT-PCR. After DNA sequencing, the gene was cloned into fusion expression vector pGEX-3X and the fusion protein of GST-Ranalexin was produced under inducement with IPTG. This expression condition was optimized under inducement with different dosages of IPTG, pH, temperature and time. Then the expressed protein was renatured by the systems of GSH and GSSG and its antibacterial activity was determined in vitro by agar diffusion method. The results indicate that the ranalexin DNA fragment at the length of 201 bp was amplified and the nucleotide homology with the sequence on GenBank was 99.57%, the recombinant plasmid pGEX-3X-Ranalexin was constructed correctly and the optimal expression condition was the IPTG final concentration of 1.0 mmol·L-1, the induction time of 5-6 h, the expressed recombinant protein existed in the form of inclusion bodies, with molecular mass of about 34 kDa. After refolding, the purified recombinant protein exhibited the antibacterial activity to Staphylococcus aureus in vitro. It is indicated that the prokaryotic expression vector for antimicrobial peptide ranalexin gene from the skin of Rana catesbiana was successfully constructed, and the recombinant antimicrobial peptide Ranalexin was prepared.